Are Long-Lived Persons Utility Monsters? - Gregory Ponthiere (Global Labor Organization (GLO), 2022)
Nozick's "utility monster" - a being who is more efficient than other persons at transforming resources into well-being - is often regarded as deeply impossible, on the ground of the incapacity of a single person to have a life that is better than a large number of other lives. In this article, I defend a purely marginalist view of the "utility monster", that is, that the primary characteristic of a "utility monster" is a higher sensitivity, at the margin, of well-being to resources, rather than a larger total well-being. I propose three purely marginalist accounts of "utility monster" and I introduce the related concept of "collective utility monster", in order to account for the collective predation of (almost) all resources by a group of persons. I argue that, although a long-lived person, if taken separately, could hardly belong to the category of "utility monster", a large group of long-lived persons can, under some conditions, belong to the category of "collective utility monster". In the light of the increasingly large proportion of cohorts reaching very old ages nowadays, Nozick's objection against utilitarianism turns out, after a thorough review, to be most relevant for real-world aging societies.
Keywords: I31; J10; J18; 330; longevity; mortality; inequalities; utilitarianism; Nozick's utility monster